Ethnic American Literatures and Critical Race Narratology - Weik von Mossner, Alexa; Mikić, Marijana; Grill, Mario (Taylor & Francis, 2023)
Ethnic American Literatures and Critical Race Narratology explores the relationship between narra¬tive, race, and ethnicity in the United States. Situated at the intersection of narrative theory and context-oriented approaches in race, ethnic, and cultural studies, it interrogates the complex and varied ways in which ethnic American authors use narrative form to engage readers in issues related to race and ethnicity. The book's international group of contributors covers a wide range of primary texts that belong to the literary traditions of Latinx, African American, Native American, Asian American, Jewish American, and Arab American communities. They demonstrate that paying attention to the formal features of these texts changes our under¬standing of narrative theory and that narrative theories can help us to think about their representations of time and space, the narration of trauma and other emotional memories, and the importance of literary (meta)paratexts, genre structures, and author functions.